INFLUENCE FROM INDIRECT REFERENCE GROUPS IN ONLINE MEDIA AFFECTING TRAVEL DECISIONS OF THAI TOURISTS IN NAKHON SI THAMMARAT PROVINCE - Ngoenkaeo, Yukhonthon (Journal of MCU Nakhondhat, 2023)
The purpose of this research paper was to 1) study the influence of indirect reference groups in online media on the travel decisions of Thai tourists in Nakhon Si Thammarat. 2) Study online media using micro-influencer to influence travel decisions in Nakhon Si Thammarat, and 3) Study online media using macro-influencer to influence travel decisions in Nakhon Si Thammarat. Use quantitative study methods The population used in the study was Thai tourists visiting Nakhon Si Thammarat. To know the exact number, the sample size was calculated for 385 people. Analyze data with statistical ready-made computer programs. The statistics used are percentage, mean, standard deviation, and linear multiple regression analysis. The study found that 78.2% of the respondents were female tourists, under the age of 30, with the highest education, a bachelor’s degree, and an average monthly income of 10,001-30,000 baht in the past 1 year. Each day trip takes a long time, and tourists often travel with their families. The influencers who affect travel decisions come from micro-influencers. The influencers who affect travel decisions come from macro-influencers and the decision to choose to travel is at a high level. Macro-influencers and micro-influencers encourage people to feel like traveling, encouraging them to make decisions easier